FRACTIONATION CHANGE OF HYDROGEN ISOTOPES IN TREES DUE TO ATMOSPHERIC POLLUTANTS - Savard M.M.; Bégin C.; Smirnoff A.; Marion J.; Sharp Z.; Parent M. (My University, 2005)
Atmospheric pollution effects on hydrogen fractionation in trees are demonstrated for the first time in this study. The δ2H ring-cellulose series obtained for black spruce trees at a site near a SO2-emitting smelter display short-term fluctuations superimposed on a first order −11‰ shift coincident with the onset of smelter operations. The isotopic depletion in trees exposed to various levels of SO2 diminish with increasing distance relative to the location of the smelter, and it is not detected at the most distant selected stand, 116 km downwind from the point source. Both the spatial and temporal isotopic trends likely result from the combined effects of leaf transpiration, biochemical processes and water uptake by the root system. The spatial and temporal trends of δ2H values are the reverse of the δ13C trends previously obtained for the same tree ring series. These coupled isotopic fractionations underline an important response of trees to pollution stresses likely generated by ambient atmospheric SO2 concentrations. The degradation of global air quality during the last 150 yr likely generated large scale modifications in the way terrestrial vegetation grows. In this respect, hydrogen dendrogeochemistry combined with other tracers such as C isotope ratios constitutes a new tool to evaluate the past behavior of forest ecosystems in terms of C uptake and acclimation to various types of atmospheric pollution.